2021
DOI: 10.3390/audiolres11010005
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Brainstem Responses to Successive Sounds: Effects of Gap Duration and Depth

Abstract: Temporal acuity is the ability to differentiate between sounds based on fluctuations in the waveform envelope. The proximity of successive sounds and background noise diminishes the ability to track rapid changes between consecutive sounds. We determined whether a physiological correlate of temporal acuity is also affected by these factors. We recorded the auditory brainstem response (ABR) from human listeners using a harmonic complex (S1) followed by a brief tone burst (S2) with the latter serving as the evok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Duda-Miloy et al reported that the duration of the gap has a suppressive impact on the wave V amplitude in response to post-gap noise burst [5]. On the other hand, Fan et al found that neither the duration nor depth of the gap influenced response amplitude; however, they observed a significant decrease in response latency with increasing gap duration or depth [17]. Similarly, Grose et al reported that in conditions where gaps were within-channel, shorter gap durations resulted in increased wave V latency and deteriorated waveform [16].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Duda-Miloy et al reported that the duration of the gap has a suppressive impact on the wave V amplitude in response to post-gap noise burst [5]. On the other hand, Fan et al found that neither the duration nor depth of the gap influenced response amplitude; however, they observed a significant decrease in response latency with increasing gap duration or depth [17]. Similarly, Grose et al reported that in conditions where gaps were within-channel, shorter gap durations resulted in increased wave V latency and deteriorated waveform [16].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that human data was only reported up to 4000 Hz. Fan et al used a harmonic complex [17].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations